2020
DOI: 10.1093/jnci/djaa048
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Coverage Disruptions and Cancer Care and Outcomes: Systematic Review of Published Research

Abstract: Abstract Background Lack of health insurance coverage is associated with poor access and receipt of cancer care and survival in the United States. Disruptions in coverage are common among low-income populations, but little is known about associations of disruptions with cancer care, including prevention, screening, and treatment, as well as outcomes of stage at diagnosis and survival. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 56 publications
4
67
0
Order By: Relevance
“…12 Among patients with cancer, Medicaid coverage disruptions are associated with later-stage diagnosis and worse survival. 13 Previous studies of populations with Medicaid coverage used Medicaid enrollment and claims data 13−15 and could not distinguish between individuals who were previously uninsured and individuals with previous private coverage. Furthermore, previous studies did not separately evaluate the disruptions in private coverage, most of which is employer-sponsored and the most common type of health insurance coverage in the working-age population.…”
Section: Introductionmentioning
confidence: 99%
“…12 Among patients with cancer, Medicaid coverage disruptions are associated with later-stage diagnosis and worse survival. 13 Previous studies of populations with Medicaid coverage used Medicaid enrollment and claims data 13−15 and could not distinguish between individuals who were previously uninsured and individuals with previous private coverage. Furthermore, previous studies did not separately evaluate the disruptions in private coverage, most of which is employer-sponsored and the most common type of health insurance coverage in the working-age population.…”
Section: Introductionmentioning
confidence: 99%
“…Many different factors contribute to these disparities including baseline socioeconomic (SES); distributions by race; access to screening and care; insurance status; tumor biology and characteristics; and differences in disease management and care delivery in various healthcare settings. Having health insurance is strongly associated with better overall survival as well as cancer-specific outcomes such as recurrence and progression-free survival [5][6][7][8][9][10][11][12][13]. Although several recent studies have examined cancer outcomes by both race/ethnicity and SES, they included both patients with and without health insurance, making it difficult to disentangle the effects of health insurance coverage from other SES factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although disparities in breast cancer deaths are measured in numbers, their impact is felt in the women who have lost their lives. A strong predictor of breast cancer death is a lack of health insurance coverage and/or interruption of health care 20‐23 . Uninsured women are less likely to receive high‐quality breast cancer screening; once diagnosed with breast cancer, uninsured women are less likely to receive evidence‐based treatment 20 .…”
mentioning
confidence: 99%
“…A strong predictor of breast cancer death is a lack of health insurance coverage and/or interruption of health care 20‐23 . Uninsured women are less likely to receive high‐quality breast cancer screening; once diagnosed with breast cancer, uninsured women are less likely to receive evidence‐based treatment 20 . A recent systemic review of health insurance coverage disruptions from 1980 to 2019 demonstrated that coverage disruptions were statistically associated with lower prevention and cancer screening, and patients with Medicaid disruptions (vs those without disruptions) were more likely to have advanced stage cancer (odds ratio, 1.2‐3.8) and worse survival (hazard ratio, 1.28‐2.43) 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation